Multitasking and mixed systems for provider payment - Eggleston, Karen (Journal of health economics, 2005)
The problem of multitasking refers to the challenge of designing incentives to motivate appropriate effort across multiple tasks when the desired outcomes for some tasks are more difficult to measure than others. Multitasking is pervasive in health care. I use a simple model to show that the problem of multitasking further strengthens conventional arguments for mixed payment systems such as partial capitation. When pay-for-performance metrics are imperfect for rewarding service-specific quality efforts, using mixed payment helps to balance incentives for quality effort across services.